Integrated sedimentary and high-resolution mineralogical characterisation of Ordovician shale from Canning Basin, Western Australia: Implications for facies heterogeneity evaluation - Iqbal, Muhammad Atif; Rezaee, Reza; Laukamp, C.; Pejcic, B.; Smith, Gregory (2022)
An understanding of the nature of the facies heterogeneity is crucial for successful exploration and development of shale reservoirs. However, shale is a very fine-grained sedimentary rock and it is challenging to understand its heterogeneity through conventional techniques. This paper addresses this challenge for Ordovician Goldwyer Formation (Goldwyer-III shale) through a unique approach by integrating core data with high-resolution image logs (SCMI); petrographic information; Fourier transform infrared (FTIR); and hyperspectral drill core reflectance spectra acquired using a HyLogger3. The petrographic and FTIR data validates the usage of HyLogger3 as a tool to examine high-resolution vertical variations in the shale mineralogy. The results indicate that the Goldwyer-III shale is highly heterogeneous in terms of sedimentary features, organic richness and mineral composition. The studied shale is divided into four facies based on colour, sedimentary features, mineral composition and lithology. The facies include thinly laminated siliceous shale (TLSh), concretionary-banded calcareous shale (CSh), massive black shale (MBSh) and heterolithic shale (HSh). The total organic carbon varies from 0.35 to 4.5 wt% due to variation in facies as a result of fluctuation in oxic-anoxic conditions. The TLSh, MBSh and HSh facies have a higher TOC value (up to 4.5 wt %), Tmax (up to 450 °C), hydrogen index (up to 250 mgHC/g) and brittleness index (>0.4) comparatively. Whereas, the CSh facies has least TOC, Tmax, hydrogen index and brittleness index. Continuous high-resolution hyperspectral core log data, combined with petrography and conventional core logging, provides a much better understanding of heterogeneity in Goldwyer-III shale. This study offers a new workflow for rapid, continuous and accurate recognition of optimum facies for hydraulic fracturing. This approach can improve economic decisions when developing shale gas reservoirs. Based on TOC and mineralogical derived brittleness index cut-offs values, the high-quality brittle zones are recognised in TLSh and HSh facies deposited in medial (proximal to distal) depositional setting.